Reflection and transmission relationship of lamb wave - Gnanasekaran Balaji. (2013)
In recent years the use of composite materials in aerospace and energy industries are increased remarkably due to the technological advancement in material engineering. The one of the challenge in using composite materials is that detecting and monitoring the defect on it. Currently in industries the ultrasonic non-destructive technique are widely used to identify the defects on composite materials. This process is time consuming and it requires structure downtime. To overcome this issues Lamb wave can be used because the Lamb wave has more travelling distance in thin plates and a potential candidate for continues monitoring of damage. It is essential to study the Lamb wave behaviour in composite materials and its interaction with defects.